ANALISIS POTENSI BAHAYA DENGAN METODE HAZARD IDENTIFICATION RISK ASSESSMENT AND RISK CONTROL (HIRARC) STUDI KASUS: PT. SAMI SURYA PERKASA - Jefri Kurniawan; Ayudyah Eka Apsari; Nancy Oktyajati, Sri Mayasari (PROSIDING, 2022)
Developments in the industrial world cause many problems that are important to study considering the potential hazards that can result in the risk of health problems and even work accidents.PT. Sami Surya Perkasa is a factory engaged in manufacturing. An industry requires an Occupational Health and Safety (K3) system with the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method which, if applied, can easily find hazardous work activities and can be carried out immediately. control according to the level of risk (urgent, high, medium, and low). This research was conducted at PT.Sami Surya Perkasa and aims to know the identification of hazards, risk assessment, and risk control, especially in the Cutting process. The results showed that there were 18 potential hazards in 13 types of work in each. Controls that can reduce the level of risk are by using Personal Protective Equipment (PPE) for workers and a safe work attitude, so that workers can safely perform work activities.The purpose of this study was to determine whether the shift workers of PT.Sami Surya Perkasa's production unit violated the rules for using PPE. Keywords: Occupational Health and Safety, Hazard Identification, Risk Assessment, Risk Control.